Attributes of the professional director: introduction - Vincent, Kellie (Henry Stewart Talks, 2019)
Boards, VUCA, Decision making, Patisserie Valerie, Attributes of board members, Leadership, Innovation, Collaboration, Hundred-year companies, Board chair